STUDI PENGGUNAAN SPEKTROSKOPI INFRAMERAH DAN KALIBRASI MULTIVARIAT UNTUK PENENTUAN PARAMETER MUTU MINYAK BUAH MERAH (Pandanus conoideus, Lam) - , LILING TRIYASMONO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A rapid method for the determination ofquality parametersof redfruit oil(RFO), namely acid value (AV), iodine value (IV) and saponification value (SV) using FTIRspectrophotometry in combination with multivariate calibration of partial least square (PLS) has been carried out.Redfruit oilwas obtained bymacerationprocess usingmethanolas extracting solvent. The methanolic extractwas partitioned using hexane andchloroform to yield hexane and chloroform fractionsof RFO, respectively. RFO without heating treatment and that heated at a temperature of100, 150, 180, 200, and300oCwerefurther assessed for its qualityparameters i.e.acid value, iodine value and saponification value using titrimetric technique based on AOAC method and FTIRspectrophotometry. Based on the optimization processes in terms of wavenumbers of the FTIR spectra of RFO samples,thewavenumber region of 1731 â 1755 cm-1was selected for determination of AV, while wavenumber region of1080 â 1114 cm-1was used foranalysis of IV.Furthermore, the SV was better determined at wavenumber regions of 1145 â 1168 cm-1. PLS calibration model was developed for the prediction of AV, IV and SV in RFO samples. The relationship between actual values of AV, IV and SV as determined using AOAC method and FTIR predicted value as determined with PLS calibration model show a close relationship with coefficient of determination (R2) of 0.998 for AV, 0.997 for IV and 0.998 for SV. The values of standard errors of calibration were 0.45 %, (v/v)0.55 % (v/v)and 0.63 % (v/v) for analysis of AV, IV and SV, respectively. This study concluded that FTIR spectrophotometric methodin combination with multivariate calibration of PLS can be used to determine the AV, IV and SV values of RFO. The developed method is simple, rapid with a total analysis time per sample of less than 3 min, and environmentally friendly.